VO2/V2O5:Ag Nanostructures on a DVD as Photoelectrochemical Sensors1. Issue 4 (28th January 2016) - Zheng, Jian; Calvillo, Laura; Rizzi, Gian Andrea; Granozzi, Gaetano
Abstract: The electrochemical deposition of a mixed oxide on the Ag nanostructured surface of a commercial digital versatile disc (DVD) is described. The VO2 /V2 O5 mixture shows interesting photoelectrocatalytic performances under visible‐light illumination after diffusion of the Ag + ions from the Ag‐DVD substrate through the layer and formation of surface vanadates, which also allows it to be applied as an inexpensive sensing device. The samples were characterized with X‐ray photoemission spectroscopy (XPS), scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), and Raman measurements. The sensing properties towards oxidizable organic substances, such as glucose, were tested. Abstract : Silver screen : We describe the electrochemical deposition of a mixed oxide on the Ag nanostructured surface of a commercial DVD. The VO2 /V2 O5 mixture shows interesting photoelectrocatalytic performance under visible‐light illumination after diffusion of Ag + ions from the Ag‐DVD substrate through the layer and formation of surface vanadates. The sensing properties towards oxidizable organic substances, such as glucose, were tested (see figure).